Vietnam socio-economic the priod 1996 - 1998 and forecast the year 2000 (Statiscal publishing house, 1999)
This book introduce the overall views on Vietnam socio-economy. Agricultural production, Expor and import activities. Foreign direct investment, some social problems. Currency crisis in Southeast Asia and experience lessons for Vietnam. Statistical data on Vietnam socio-economy, 1990 - 1998.